Pemanfaatan Biogas dari Limbah Tahu Bersama Masyarakat dan Mahasiswa Universitas Teuku Umar - Kiswanto Kiswanto; Wintah Wintah (Universitas Teuku Umar, 2025)
Tofu is a traditional food of most Indonesian people, besides the low price, it is also easy to make, but the waste produced from this process is quite polluting the environment due to the odor caused and various diseases will arise due to waste disposal that pays less attention to environmental aspects, along with the times of problematic tofu liquid waste can now be used for biogas. This service aims to find out how to process tofu liquid waste into biogas. The method of implementation is the manufacture of tofu waste reservoirs to drum reactors. The community service that the author applies uses a very simple method using used drums and hose pipes connected to the stove. The utilization of natural materials, namely tofu liquid waste in Purwosari Village, Kuala Pesisir District, Nagan Raya, is waste that is not utilized, just thrown away. The results obtained that fermented tofu waste can be used for biogas. Therefore, this service is very helpful to improve the economy of the people in the village, in addition to opening up jobs, also spending on households becomes less. So that the community is prosperous.